An Exploration of Secondary School Science Teacher’s Epistemological Belief in Malang - Safitri, Anindyta Nur Rizkyana; Purwaningsih, Endang; Munfaridah, Nuril; Darmawan, Alif (Jurnal Pendidikan Sains, 2024)
The objective of this study is to delve into the epistemological convictions of secondary school science teachers in Malang across various tenures, namely senior teachers, junior teachers, and pre-service teachers. Employing an explanatory sequential design model, the research employs a mixed-method approach. Quantitative data, gathered through the administration of the Scientific Epistemology Beliefs Questionnaire (n = 30), are complemented by qualitative insights drawn from interviews with teachers (n = 6) concerning their epistemological orientations. Descriptive statistics and qualitative analyses, utilizing an a priori coding technique aligned with the study’s conceptual framework, were conducted on the interview data. Quantitative analysis reveals a parity in the level of epistemological beliefs among teachers. However, qualitative examination unveils nuanced distinctions: senior teachers demonstrate transitional epistemological beliefs, while junior teachers and pre-service teachers exhibit traditional and instructive orientations, respectively. These findings hold significance for the enhancement of teachers’ professional development in Malang, particularly in the domain of science pedagogy.DOI: 10.17977/jps.v12i12024p034